Personification in Call Us What We Carry Poems by Amanda Gorman 2021 - Hafizh Assad; Devi Hellystia (J-Lalite: Journal of English Studies, 2022)
This research is supposed to find the types of personification and to know which personification types are dominant in Call Us What We Carry poems by Amanda Gorman. The previous research has emphasized the types, meanings, and functions of personification contained in literary work. The qualitative research method was used in this research. The data of this research were lines and stanzas which personification form is contained within the poem. This research used the types of personification theory by Breen (2021) to analyze the types of personification in the poem. The results of this research showed 3 types of personification which contained 51 data of personification types in total. The Platonic personification type which applied an action, picture, and the role of human knowledge into an inanimate object includes a total of 46 data was the most dominant of the three forms of personification since its characteristics most frequently occur in the lines and stanzas of Call Us What We Carry poems. Then, it is followed by the Prudentian personification type that has religious and deification aspects in their characters with a total of 3 data; it is uncommon to discover lines and stanzas in the Call Us What We Carry poems by Amanda Gorman that fulfill the features of Prudentian personification. The last position was occupied by the Aristotelian personification type which has a mundane and ironic characteristic. This personification type contained the least quantity of 2 data due to the rarity of lines and stanzas.